Relationship of psychological time with elements of movie's expression Example) movies, which their events takes, place in one day / as) (Al-Academy, 2016)
This research deals with and which was entitled: relationship between psychological time and elements of filming expression (one-day event filmsas an example). It is about the relationship of psychological time (internal) with the elements of filming expression and how the time affected when using these elements in terms of its deceleration or acceleration. In particular, this research focus on elements that slow down time or stops it when using these elements. As one day time is short and heavy at the time of spectators in terms of the large number of film events which makes the viewer runs out of breath to understand the nature of those events and then identify the causes and consequences, as they occur in a short time (one day time) and make the viewer wonder and doubt; are all these events already occur in such a short time? Based on that, the director and especially in films that takes place in one day, deliberates to the use of certain filming elements to decelerates time or (extend it) and stop it. But of course, these filming elements are not already provide or stop time, it happens psychologically to the personality of the actor that acting the role or the viewer, or for both them The research is divided into four chapters Chapter 1 includes : methodological framework; which presents the problem of search, and brings the following question; What is the relationship of the elements of filming expression with the psychological time ? The goal is to reveal the relationship between the elements of filming expression to the psychological time . The second chapter covered the theoretical framework, the first topic includes: the psychological time and elements of filming expression . The second topic: the dramatic and expressive dimension in one day time film, The third chapter covered research procedures, and methodology and its tool, as the theoretical indicators that came out of theoretical framework, The research sample has included one novel films that take place in one day; (Eternal and a Day) for the Greek director Theo Angelopoulos. The fourth chapter includes the analysis and results